Gas Turbines A Handbook of Air, Land and Sea Applications. - Soares, Claire (Butterworth-Heinemann, an imprint of Elsevier, 2015)
Covering basic theory, components, installation, maintenance, manufacturing, regulation and industry developments, Gas Turbines: A Handbook of Air, Sea and Land Applications is a broad-based introductory reference designed to give you the knowledge needed to succeed in the gas turbine industry, land, sea and air applications. Providing the big picture view that other detailed, data-focused resources lack, this book has a strong focus on the information needed to effectively decision-make and plan gas turbine system use for particular applications, taking into consideration not only operat.
Keywords: Gas-turbines.; elektronické knihy; electronic books